Relationship Between Functional Classification Systems in Children With Cerebral Palsy - Azade Riyahi; Zahra Nobakht; Farin Soleimani; Nahid Rahmani; Firoozeh Sajedi (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective: Cerebral palsy refers to a group of postural and movement disorders that limit movements and can be related to a non-progressive disorder in the developing brain. The international classification of disability emphasizes the child's functional abilities and routine performance. Some classification tools have been developed to describe and evaluate child's functions in daily activities such as walking, manipulating objects, and everyday communication. The present study aimed to investigate the relationship between classification systems (gross motor function, manual ability, communication function, and eating and drinking ability) in children with cerebral palsy. Materials & Methods: This study was performed by cross-sectional correlation method and of descriptive analytical type. Children with cerebral palsy aged 12-144 months were recruited by convenience sampling from patients referred to clinics and public and private rehabilitation centers in Tehran and Arak cities, Iran, in 2019-2020. After completing the demographic information questionnaire by the child's primary caregiver, the gross motor function classification system (GMFCS), manual ability classification system (MACS), Communication function classification system (CFCS), and eating and drinking ability classification system (EDACS) were completed by a child therapist.  Results: In the present study, 154 children with a Mean±SD age of 49.45±32.22 months participated. also, 87 children (56.5%) were boys, and 67(43.5%) were girls. According to GMFCS, the highest percentage distributions at levels II and IV were 31.2% and 26%, respectively. In other words, more than 57% of children were distributed in these two levels. According to MACS, the distributions of the highest percentages at levels II, III, and IV were 28.6%, 22.1%, and 20.8%, respectively. In other words, more than 70% of the children were distributed in these three levels. According to EDACS, the distribution of almost all levels was equal except the V level, with 4.3% having the lowest percentage. According to CFCS, the distribution of the highest percentage at levels V and IV was 23.5%. In examining the relationship between functional systems, significant relationships were observed in all cases: MACS and GMFCS, r=0.672; CFCS and GMFCS, r=0.581; EADCS and GMFCS, r=0.593; CFCS and MACS, r=0.555; EADCS and MACS, r=664; EADCS and CFCS, r=0. 547 (P<0.01). Conclusion: It seems that children with more motor function limitations show more limitations in other performance classification systems, too. Of course, the number of studies in this field is limited and needs further investigation.